Pivoting Lean Manufacturing through Industry 4.0 in the Indian Context - Basu, Protik; Dan, Pranab K. (Asian Journal of Engineering and Applied Technology, 2019)
Industry 4.0 and lean management both focus on increasing productivity of industrial systems. Industry 4.0 is foreseen to revolutionize today’s manufacturing environment whereas lean management is an integrated techno-operational system which has gained increasing importance in recent times to bring about a competitive state in an organization. Though in the last three decades there have been rigorous studies on lean manufacturing (LM), its implementation in the Indian manufacturing domain is still in its nascent stage. A lack of research to explore the potential use of Industry 4.0 is also noted. Research work on the compatibility of Industry 4.0 with LM is scarce and any study on the role of Industry 4.0 on LM in the Indian manufacturing sector is practically unavailable. The aim of this research is to explore how the fourth industrial revolution, referred to as Industry 4.0, can strategize LM in the Indian manufacturing context. Empirical studies have disclosed that Indian managers are hesitant to go for automation and technological developments. Results of this work reveal that there needs to be a change in attitude and approach. Lean implementers in India need to embrace Industry 4.0 to pivot LM by automating through Cyber-Physical Systems and creating a flexible design and production model of customized and smart products.